Searching for something familiar or novel: top-down attentional selection of specific items or object categories. - Wu, R; Scerif, G; Aslin, R; Smith, T; Nako, R; Eimer, M (2013)
Visual search is often guided by top-down attentional templates that specify target-defining features. But search can also occur at the level of object categories. We measured the N2pc component, a marker of attentional target selection, in two visual search experiments where targets were defined either categorically (e.g., any letter) or at the item level (e.g., the letter C) by a prime stimulus. In both experiments, an N2pc was elicited during category search, in both familiar and novel contexts (Experiment 1) and with symbolic primes (Experiment 2), indicating that, even when targets are only defined at the category level, they are selected at early sensory-perceptual stages. However, the N2pc emerged earlier and was larger during item-based search compared with category-based search, demonstrating the superiority of attentional guidance by item-specific templates. We discuss the implications of these findings for attentional control and category learning.